The Pharmacokinetics and Pharmacodynamics of Buprenorphine in Neonatal Abstinence Syndrome. Issue 6 (28th April 2018) - Moore, Jason N.; Gastonguay, Marc R.; Ng, Chee M.; Adeniyi‐Jones, Susan C.; Moody, David E.; Fang, Wenfang B.; Ehrlich, Michelle E.; Kraft, Walter K.
Abstract : Neonatal abstinence syndrome (NAS) is a condition affecting newborns that are exposed to an opioid in utero . In a randomized, controlled trial assessing the efficacy of buprenorphine and morphine in NAS, blood samples were analyzed from a subset of patients receiving buprenorphine along with NAS scores. The data were used to validate and adapt an existing model of buprenorphine in neonates and to identify relationships between buprenorphine or norbuprenorphine pharmacokinetics (PK) and efficacy or safety. The time to NAS stabilization was found to decrease with increasing buprenorphine exposure. This pharmacokinetic–pharmacodynamic (PK‐PD) relationship was able to be quantified and adequately described with a mathematical model. The findings confirm a previous PK model of buprenorphine and extend the model to describe the PK of norbuprenorphine and to identify a novel PK‐PD relationship of buprenorphine in NAS. This model will allow optimization of dosing strategies in future clinical trials.